The Trophic Status and Fish Potential Yield of Ayamaru Lake in West Papua, Indonesia - Taufiq Hidayah; Marson Marson; Dina Muthmainnah; Ni komang Suryati (Program Pascasarjana Universitas Sriwijaya, 2021)
Ayamaru lake is a shallow lake located in the Maybrat district, West Papua which has a significant role in supporting the water supply, transportation, tourism, fisheries, and transit area for the migratory bird. The data and information of the trophic status and the fish potential yield in this lake should be understood before making any decisions for effective resource management to enhance fish production. The study was conducted in March and July 2019 in five sampling sites of Ayamaru lake, West Papua. Three water quality parameters were sampled for this study namely transparency, chlorophyll-a, and total phosphate. Moreover, these three parameters were used to calculate the Trophic State Index (TSI) and Fish Potential Yield. The result showed that based on the TSI value, the Ayamaru lake was categorized as a mesotrophic lake supported by its clear water. This waterbody has a fish potential yield of 56.33 kg/ha/year or 55.2 ton/year.